(3CQLhRI aj YdGeGJ GdehJs - (3GHbQGW GdMcjes
(3ChdgG (B:s
(3jG QH de jRd eNRhfG ecJeG Hjf GdhQi ecfhfG ai UMH eMLhHI eWhjI eVehfI eSJhQI eNajI s
(3BNQgG (B:s
(3agPg LedI eG cGf fNQ ef SQ HbQGW GdMcje GdeYJHQ aGMaXg Ef cfJ MajXkG ddMce hCfJ ai GdWH QajY cGdYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B82 - (3U(B189s
(3GfXQgG eY CQLhRI ai GdWH dGHf SjfG Qbe (B301 (3fSNI BjI Gddg GdMcje GdYGeIs
(3hGfXQ CQLhRI ai fXe GdbVGjG GdNeSI Qbe (B306- 380-382s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B15 s
Keywords: (3GdWHs